Use of the 13-valent pneumococcal conjugate vaccine in children and adolescents aged 6 – 17 years. (October 2013) - Mitchell, Ruth; Trück, Johannes; Pollard, Andrew J
Abstract : Introduction: The introduction of pneumococcal conjugate vaccines into infant immunization schedules has successfully reduced the incidence of pneumococcal disease caused by vaccine serotypes. Disease incidence is low in healthy 6 – 17-year-old children and young people; however, there are a number of clinical conditions that put individuals in this age group at increased risk. Expansion of the license of a13-valent pneumococcal conjugate vaccine, PCV-13, to include the 6 – 17 age group has recently been approved by European and American regulatory bodies. Areas covered: Studies assessing the safety, immunogenicity, and efficacy of pneumococcal conjugate vaccines in both healthy and high-risk 6 – 17-year-old children and adolescents are covered and the potential impact of PCV-13 in these populations is discussed. The use of the 23-valent pneumococcal polysaccharide vaccine, PPV-23, in high-risk children and adolescents is also considered. Expert opinion: Expanding the use of PCV-13 to include high-risk children and adolescents aged 6 – 17 has the potential to prevent additional cases of disease; however, vaccination of this population may no longer be necessary when herd immunity to PCV-13 serotypes becomes fully established. Despite the broader serotype coverage of PPV-23, the benefits of this vaccine in high-risk populations are uncertain.